The effect of human resource competency, communication, and technology on government’s statement - Maryati Kadir Thalib, Syamsuri Rahim, Hamzah Ahmad,; Abu Thalib, Jasmi (Opción, 2019)
This study examines the effect of human resources, Information and Communications Technology (ICT) and government internal control systems on the quality of regional government financial statements. This study uses primary data that will be gathered by using questionnaires and interviewing the informant. As a result, the effectiveness of government internal control system can contribute to mediating the qualified human resource, ICT and coercive power to improve the quality of financial statements of North Gorontalo. In conclusion, the qualified human resource, ICT and coercive power also partly significant in improving the quality of financial statement of North Gorontalo.